Tiagabine in the maintenance treatment of bipolar disorders. - Young, A; Geddes, J; Macritchie, K; Rao, SN; Vasudev, A (2006)
BACKGROUND: Tiagabine, an anticonvulsant, has been reported to have efficacy in prophylactic treatment of bipolar disorder in case reports and in case series. OBJECTIVES: To review the efficacy and acceptability of tiagabine, relative to placebo, and other agents in the prevention and/or attenuation of episodes of bipolar affective disorder. The efficacy and acceptability of tiagabine were considered in terms of mood symptoms, mortality, general health, social functioning, adverse effects and overall acceptability to patients. SEARCH STRATEGY: The following databases were searched on 13-10-2005. The Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Registers (CCDANCTR-Studies and CCDANCTR-References),The Cochrane Controlled Clinical Trials Register (CCCTR),EMBASE,MEDLINE,LILACS,PsycLIT andPsyndex. Reference lists of relevant papers and major textbooks of affective disorder were examined.Authors, other experts in the field and pharmaceutical companies were contacted for knowledge of suitable published or unpublished trials. Specialist journals and conference proceedings were handsearched. SELECTION CRITERIA: Randomised controlled trials which compare tiagabine with placebo, alternative mood stabilisers or antipsychotics, where the stated intent of intervention was the maintenance treatment of bipolar affective disorder, were sought. Bipolar patients, male and female, of all ages were to be included. DATA COLLECTION AND ANALYSIS: Data were to be extracted from the original reports if they met our inclusion criteria. The main outcomes to be assessed were:(1) The efficacy of tiagabine treatment in preventing or attenuating further episodes of bipolar affective disorder, including its efficacy in rapid cycling disorder.(2) The acceptability of tiagabine treatment to patients.(3) The prevalence of side effects.(4) Mortality, if any, on tiagabine treatment.Outcomes concerning relapse or recurrence were to be analysed excluding data from studies using discontinuation protocols, which were to be analysed separately. Sub-group analyses were to be performed to examine the effects of tiagabine treatment in rapid cycling bipolar disorder and previous mood stabiliser non-responders. Data were to be analysed using Review Manager version 4.2.8. MAIN RESULTS: No randomised controlled trials of tiagabine in the maintenance treatment of bipolar disorder were found. AUTHORS' CONCLUSIONS: There is an insufficient methodologically rigorous evidence base to provide guidance on the use of tiagabine in the maintenance treatment of bipolar disorder. There is a need for randomised controlled trials examining the therapeutic potential of this agent in bipolar disorder, after the nature of reported episodes of syncope or seizure in tiagabine-treated bipolar patients has been established.